Sociocultural Learning Model for Empowering Sustainable Development Education in Islamic Boarding Schools through Local Cultural Contexts - Mgs. Muhammad Farouq; Rachmat Kriyantono; Muhammad Lukman Hakim; Sahiruddin (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2024)
Sustainable development has become an important concern for educational institutions around the world, with a growing emphasis on the integration of socio-cultural perspectives into the curriculum. This paper presents a critical analysis of the role of socio-cultural education in promoting education for sustainable development (ESD) within pesantren settings. It explores the key issues and challenges surrounding the incorporation of socio-cultural elements based on local wisdom. This research is entitled "Sociocultural Learning Model for Empowering Sustainable Development Education in Islamic Boarding Schools through Local Cultural Contexts: Case Study at IGM Al-Ihsaniyah Islamic Boarding School Palembang". The main focus of this research is to analyze the implementation and find a suitable model for ESD-based Sociocultural Learning. This research uses a qualitative method with an intrinsic case study, exploring in depth how the concept of ESD is implemented in the pesantren environment. The informants in this study consisted of 5 people who were residents of the pesantren. The results showed that the integration of ESD in the pesantren curriculum has great potential to strengthen character values, independence, and environmental awareness among students. The main supporting factors in this implementation are the support from the pesantren leadership, active participation from the pesantren environment, and the availability of adequate facilities and infrastructure. However, the study also found a number of barriers such as the limited understanding and awareness of educators regarding the concept of ESD, as well as the lack of resources and policy support that supports the implementation of ESD. These findings have implications for the importance of developing a Sociocultural learning model that is more comprehensive and adaptive to local needs in responding to the challenges of the Sustainable Development Goals (SDGs).